Nanoparticles targeting hematopoietic stem and progenitor cells: Multimodal carriers for the treatment of hematological diseases - Cruz, Luis J.; Rezaei, Somayeh; Grosveld, Frank; Philipsen, Sjaak; Eich, Christina (Frontiers in Genome Editing, 2022)
Modern-day hematopoietic stem cell (HSC) therapies, such as gene therapy, modify autologous HSCs prior to re-infusion into myelo-conditioned patients and hold great promise for treatment of hematological disorders. While this approach has been successful in numerous clinical trials, it relies on transplantation of ex vivo modified patient HSCs, which presents several limitations. It is a costly and time-consuming procedure, which includes only few patients so far, and ex vivo culturing negatively impacts on the viability and stem cell-properties of HSCs. If viral vectors are used, this carries the additional risk of insertional mutagenesis. A therapy delivered to HSCs in vivo, with minimal disturbance of the HSC niche, could offer great opportunities for novel treatments that aim to reverse disease symptoms for hematopoietic disorders and could bring safe, effective and affordable genetic therapies to all parts of the world. However, substantial unmet needs exist with respect to the in vivo delivery of therapeutics to HSCs. In the last decade, in particular with the development of gene editing technologies such as CRISPR/Cas9, nanoparticles (NPs) have become an emerging platform to facilitate the manipulation of cells and organs. By employing surface modification strategies, different types of NPs can be designed to target specific tissues and cell types in vivo. HSCs are particularly difficult to target due to the lack of unique cell surface markers that can be utilized for cell-specific delivery of therapeutics, and their shielded localization in the bone marrow (BM). Recent advances in NP technology and genetic engineering have resulted in the development of advanced nanocarriers that can deliver therapeutics and imaging agents to hematopoietic stem- and progenitor cells (HSPCs) in the BM niche. In this review we provide a comprehensive overview of NP-based approaches targeting HSPCs to control and monitor HSPC activity in vitro and in vivo, and we discuss the potential of NPs for the treatment of malignant and non-malignant hematological disorders, with a specific focus on the delivery of gene editing tools.